(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Article 371J in the Indian Constitution passed in 2012 to address historical socio-economic disparities in what is called Kalyana Karnataka. Here we explore the effects of this provision on political mobilization in the region across the last decade. It claims that Article 371J has served as a spur for higher political awareness and participation, albeit its impact is complex. It responded by bringing the excluded purposefully in, fostering a new generation of political actors and civil servants, through the reservation of seats in educational institutions and jobs in government. This has increased demands for accountability and responsiveness from elected officials. The paper demonstrates the impact of article 371J on electoral dynamics, the emergence of regional political movements, and the expression of regional grievances. The provision has opened the door to marginalized voices, but that has also posed challenges. Focusing on specific groups of people could inadvertently widen the existing social divide. Most importantly, political mobilization will depend on factors that are not even covered under Article 371J, such as the availability of information and resources. This paper examines these complexities by utilizing empirical data and case studies to evaluate the multifarious consequences of Article 371J on political mobilization in Kalyana Karnataka. The paper concludes by highlighting the implications for democratic participation and regional development, and the importance of ensuring continued efforts towards inclusive and equitable political processes.